Revisiting Retrograde Ventriculosinus Shunt as an Alternative for Treating Hydrocephalus in Children - Oliveira, Matheus Fernandes; Teixeira, Manoel Jacobsen; Oliveira, Marcelo Lima; Shu, Edson Bor Seng; Pinto, Fernando Campos Gomes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Retrograde ventriculosinus shunt (RVSS) is a useful option in the daily routine of neurosurgeons dealing with hydrodynamics. The objective of this manuscript is to review the main data about RVSS.Methods We performed a critical review. The keywords used were hydrocephalus, shunt, venous sinus, ventriculosinus shunt, retrograde ventriculosinus shunt, and sagittal sinus. The search was performed in the Medline (Pubmed) and EMBASE databases.Results Van Canneyt et al (2008) and Pinto et al (2016) performed experimental studies confirming the effectiveness of RVSS. El Shafei et al (1985, 1987, 2001) authors reported several cases treated with efficacy and few complications. Oliveira et al (2015, 2016) compared RVSS and ventriculoperitoneal shunt (VPS) in the treatment of hydrocephalus after myelomeningocele repair in infants, with similar functional results. Oliveira et al (2015, 2016) also described the applicability of RVSS in situations when VPS is not feasible, or when the peritoneum is not useful.Discussion Retrograde ventriculosinus shunt is a safe and more physiological option, which requires the use of less prosthetic material. It is feasible and applicable. Especially in children, it generates a normotensive state after shunting, allowing centrifugal head growth, once there is no intracranial hypotension due to overdrainage, which may reflect in long-term better psychomotor development.Conclusions The surgical technique of RVSS is feasible. The clinical results are comparable with those of the VPS.
Keywords: hydrocephalus; ventriculosinus shunt; treatment; review